Veden virtaukset pilveen teknologian avulla - Launonen, Susanna (2025)
This study examines the role of the Teltonika TRB256 gateway in transmitting water consumption data to the cloud as part of the Smartvatten system. The study evaluates the gateway’s performance from the perspective of data transmission and programming languages. The objective of the research was to determine how different programming languages and data transmission protocols affect the gateway’s performance and how the transmission of water consumption monitoring data can contribute to optimizing water usage.